The Analysis of The Strategy of Indonesia National Police in Facing Homecing in Indonesia during Pandemic (A Case Study on Homecoming 2021) - Ardian Dirgantara (Jurnal Ilmu Kepolisian, 2022)
The aim of this paper is to define and compare provided sources in terms of defining the concept of Strategy and Performance in organisations and implementing a suitable framework in the collaboration case study. This outline will be in three parts. First, the collaboration case study is outlined in detail. Second, a definition of strategic management in organisations is provided. Third, the concept of performance management in organisations is explored. The case study that will be used in this paper covers the strategies employed by the Indonesian National Police (INP), the Covid-19 Response Acceleration Task Force (Satgas) and the Provincial & Regional government during the Islamic religious event “Pulang Kampung”, or homecoming, that is held annually by the majority of Indonesian’s Muslim population. The analysis is conducted by using a PESTEL and SWOT analysis, a Strategy Map, and a Performance Domain approach to examine the external and internal factors that emerged.Keyword: homecoming, PESTEL analysis, police strategy, strategic management, SWOT Analysis